Sinergi Entrepreneurship dan Digital Marketing: Analisis Literatur terhadap Model Bisnis Berbasis Platform Digital - Ismayunita Ismayunita; Melda Hamdi; Nisha Ananda; Mhd Rizki Ramadhan; Sri Wulan Dari; Muhammad Riansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the synergy between entrepreneurship and digital marketing in developing digital platform-based business models through a literature review approach. The main problem raised is the lack of systematic integration of entrepreneurship and digital marketing concepts in building sustainable digital business models. This study uses a literature review method with a descriptive qualitative approach to journal articles, academic books, and scientific proceedings published in the 2020–2025 period. Literature sources were obtained from the Google Scholar, ScienceDirect, Scopus databases, and accredited national journal portals. The analysis was conducted using thematic analysis techniques to identify patterns, key concepts, and relationships between relevant variables. The results of the study indicate that the synergy between entrepreneurship and digital marketing plays a crucial role in creating competitive advantage for digital platform-based business models, particularly through the use of technology, value innovation, and data-driven market orientation. Successful digital business models are characterized by the entrepreneur's ability to integrate creativity, digital technology, and platform-based marketing strategies. The study's conclusion confirms that collaboration between entrepreneurship and digital marketing is a key factor in increasing the sustainability and scalability of digital businesses in the platform economy era.